Disfunção renal nos primeiros anos de vida em prematuros de muito baixo peso - Pasini, Laís Fagundes (My University, 2025)
Objective: To identify factors, particularly neonatal acute kidney injury, associated with an increased risk of developing chronic kidney disease (CKD) within the first 10 years of life in children with a history of prematurity and very low birth weight (VLBW). Methods: This nested case-control study was conducted on VLBW infants (>500g and <1.500g) born between 2012 and 2022. The population (n= 119) included children who developed CKD (n=55) and controls with normal findings (n=64). CKD was defined by abnormal blood pressure, reduced glomerular filtration rate, or elevated urinary albumin excretion. Data on neonatal and maternal factors were analyzed using logistic regression to identify predictors of CKD. Results: Of the 267 eligible children 119 were included, with a median age of 32 months, and median gestational age and birth weight of 30 weeks and 1170g, respectively. Children with CKD had lower birth weight Z-scores (-1.06 vs. -0.89), a higher occurrence of extrauterine growth restriction (EUGR) (72% vs. 51%) and an increased likelihood of maternal preeclampsia exposure. Maternal preeclampsia was identified as an independent predictor of CKD, associated with a 5% increase in the odds of developing the condition (OR 1.05, 95% CI 1.01?1.66). Conclusion: Maternal preeclampsia was associated with CKD in children with a history of VLBW. This finding highlight the importance of long-term follow-up and early identification of at-risk individuals. [resumo fornecido pelo autor]
Objetivo: Identificar fatores, particularmente a lesão renal aguda neonatal, associados ao aumento do risco de desenvolver doença renal crônica (DRC) nos primeiros 10 anos de vida em crianças com história de prematuridade e muito baixo peso ao nascer (MBPN). Métodos: Este estudo de caso-controle foi realizado em RNMBP (>500g e <1.500g) nascidos entre 2012 e 2022. A população (n= 119) incluiu crianças que desenvolveram DRC (n=55) e controles com achados normais (n=64). A DRC foi definida por pressão arterial anormal, taxa de filtração glomerular reduzida ou excreção urinária de albumina elevada. Os dados sobre fatores neonatais e maternos foram analisados por meio de regressão logística para identificar preditores de DRC. Resultados: Das 267 crianças elegíveis foram incluídas 119, com mediana de idade de 32 meses, mediana de idade gestacional e peso ao nascer de 30 semanas e 1170g, respectivamente. As crianças com DRC apresentaram menores escores Z de peso ao nascer (-1,06 vs. -0,89), maior ocorrência de restrição de crescimento extrauterino (RCEU) (72% vs. 51%) e maior probabilidade de exposição materna à pré-eclâmpsia. A pré-eclâmpsia materna foi identificada como um preditor independente de DRC, associada a um aumento de 5% nas chances de desenvolver a condição (OR 1,05; IC 95% 1,01-1,66). Conclusão: A pré-eclâmpsia materna foi associada à DRC em crianças com história de MBPN. Esse achado destaca a importância do acompanhamento em longo prazo e da identificação precoce de indivíduos em risco. [resumo fornecido pelo autor]
Keywords: Nascimento prematuro; Retardo do crescimento fetal; Injúria renal aguda; Insuficiência renal crônica; Prematuros - Doenças; Premature birth; Fetal growth retardation; Acute kidney injury; Renal Insufficiency, Chronic; Infants (Premature) - Diseases